МНОГОКРИТЕРИАЛЬНЫЙ ВЫБОР ОПТИМАЛЬНЫХ СРЕДСТВ ТЕЛЕКОММУНИКАЦИЙ - Безрук, Валерий Михайлович; Скорик, Юлия Валериевна; Чеботарёва, Д. В. (Збірник матеріалів Міжнародної науково-технічної конференції «ПЕРСПЕКТИВИ ТЕЛЕКОМУНІКАЦІЙ», 2016)
Multicriterial choice of optimal telecommunications means Theoretical and practical aspects of choosing the optimal version of telecommunications means taking into account the totality of quality indices are considered.